Association between post-traumatic stress disorder levels and serum inflammatory factors in patients undergoing digit replantation - Ge, Lei; Ju, Hui; Liu, Bing; Ma, Chao; Cheng, Zhongrong; Cui, Panpan; Liu, Wencong (Frontiers in Neuroscience, 2026)
ObjectiveTo investigate the levels of early postoperative post-traumatic stress disorder (PTSD) and their association with serum inflammatory factors in patients undergoing digit replantation, and to analyze the influencing factors.MethodsA total of 96 patients who underwent digit replantation at Rizhao People’s Hospital between March 2022 and December 2024 were enrolled 7 days postoperatively. PTSD levels were assessed using the PTSD Checklist-Civilian Version (PCL-C). Morning fasting blood samples were collected, and serum levels of interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-6, and IL-10 were measured by ELISA. Data were analyzed using univariate analysis, Spearman’s correlation, multiple linear regression, and Receiver Operating Characteristic (ROC) curve analysis.ResultsThe mean PCL-C score for the 96 patients was 38.21 ± 9.31, with 44 patients (45.83%) presenting PTSD symptoms. Univariate analysis revealed that gender, education level, injury type, complete amputation, involvement of the dominant hand, and number of amputated digits significantly influenced PCL-C scores (p < 0.05). PCL-C scores showed positive correlations with both anxiety and depression scores (r = 0.285 and 0.679, respectively, p < 0.01). Multiple linear regression identified gender, education level, complete amputation, number of injured digits, and levels of anxiety and depression as independent influencing factors for PTSD (p < 0.05). Correlation analysis indicated that PCL-C scores were positively correlated with IFN-γ, TNF-α, IL-1β, and IL-6 levels (r = 0.581, 0.521, 0.552, and 0.507, respectively), and negatively correlated with IL-10 (r = −0.474, p < 0.01). ROC curve analysis suggested that serum inflammatory factors have good predictive value for PTSD.ConclusionPatients exhibit a certain degree of PTSD in the early stage after digit replantation. Its occurrence is closely associated with female gender, lower education level, severity of the trauma, and co-morbid anxiety and depression, and is significantly correlated with an imbalance between pro-inflammatory and anti-inflammatory serum factors. Serum inflammatory factors may serve as potential biological markers for the early identification of PTSD risk.